Hydraulic control systems - Manring, Noah; Fales, Roger (Wiley, 2020)
"Hydraulic Control Systems, Second Edition is a significantly updated new edition of the must-have textbook for students and engineers in fluid power. It has been updated to cover advances in control systems, including hybrid transmissions, multi-circuit systems, health monitoring, and digital hydraulics. A new chapter on auxiliary components is included and advanced control techniques including estimation, observability, and health monitoring are also considered. Hydraulic Control Systems, Second Edition covers the fundamentals of fluid properties, fluid mechanics and dynamic systems and controls, and discusses hydraulic control systems and hydraulic components. Examples and homework problems are included throughout and a solutions manual is available on a companion website"--